PERHITUNGAN MASSA KLASIK SOLITON - ALHIDAYATUDDINIYAH T.W (LPPM, 2016)
This study aims is to describes the mass of the classical soliton solutions by using Sine-Gordon equation. the method used in this research is literature study by performing calculations through the stages of the calculation of the classical mass density of the Lagrangian and Hamiltonian. This resulting classical mass differ depending on each trial value of D from a given Lagrangian. There are convergent with the condition of mass greater than zero and some are divergent. Soliton solutions of the Sine-Gordon equation shows that the soliton behaves as a relativistic particle. Wave phenomena such as these play an important role in relation to the nature of the particles through nonlinear wave equations.Keyword: Sine-Gordon equation, soliton solutions, the classical mass.